STRUCTURE OF THE FERKESSEDOUGOU BATHOLITH (SECTOR OF ZUENOULA, CÔTE D'IVOIRE) : IMPLICATIONS ON THE INTERPRETATION OF THE GEODYNAMIC OF WEST AFRICAN PALEOPROTEROZOIC AT 2.1 Ga - (:unkn) unknown (My University, 1998)
In the West African Craton, the 2.1 Ga period is a major stage of leucogranite production. Because of its localization, its extension as much as its history in the geological literature, the batholith of Ferkessédougou (Côte d'Ivoire) is a main element for the interpretation of the Paleoproterozoic geodynamics. Interpreted as a typical granite of eugeosynclinal then as typical of collision of the modern type, it is in any case a NNE-SSW oriented significan crustal accident of Paleoproterozoic : the GFB (Greenville-Ferkessédougou-Bobodioulasso) lineament. Its study and its interpretation fall under the debate of the validity of plate tectonics at this period. As a matter of fact, by remote sensing, we show that this 400 km lenght batholith on about fifty broad consist in an important quantity of adjacent plutons which are petrographically relatively close. The general context of slightly deformed and epizonal metavolcanic and/or metasedimentary birimian age (2.2 Ga to 2.1 Ga) host rocks, as well as the absence of additional tangential deformations express the weakness of the crustal thickening synchronous of its genesis. Its fabric, determined by traditional structural analysis ans AMS (Anisotropy of Magnetic Susceptibility), is double. The first foliation (magmatic) is generally coaxial with varied orientation and dips. This foliation draws curved trajectories and expresses the intrusion of plutons. It is the equivalent of what was brought back to the D1 deformation around older granites. The second foliation (from magmatic to post-solidus), which is much better well-ordered and often constrictive or none coaxial, is the result of a regional strain transcurrent field which refers to the D2 deformation. This latter is well-known in the chrology of the birimian craton. The plutons of the granitic batholith of Ferké are syntectonic of the birimian main shortening (2.1 to 2.07 Ga). From the review of the various models of plutons emplacement, the analy
Keywords: African Research